Analisis Kinerja Keuangan Daerah Pada Pemerintah Daerah Kabupaten Sikka Tahun Anggaran 2019 – 2023 - Yohanes Frederik Gesi Kedang; Andreas Rengga; Konstantinus Pati Sanga (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The research aim was to examine the regional financial performance of the Local Government of Sikka Regency. This research employed a descriptive quantitative method. The population of this study consisted of Budget Realization Reports (APBD) of the Local Government of Sikka Regency, with the sample covering five fiscal years from 2019 to 2023. Data were collected through documentation. The financial performance of the Local Government of Sikka Regency, as measured by the independence ratio, was categorized as very low with an instructive relationship pattern, where the role of the central government was more dominant than the independence of the local government. The effectiveness of the regional financial performance of Sikka Regency in 2019 – 2023 had an average of 85,90%, which fell into the less effective category. The allocation of funds in Sikka Regency was still unbalanced, as most of the APBD was allocated to operational expenditures with an average of 68,48%, while capital expenditures accounted for only an average of 13,4%. The revenue growth of the Sikka Regency Government from 2019 to 2023 tended to fluctuate, which occurred due to the suboptimal revenue received by the local government